Insulin injection site and time interval administration for the postprandial glucose control in patient with diabetes type 2: A randomized clinical trial - Agus Santosa; Danong Erdiawan; Elsye-Maria Rosa (Tehran University of Medical Sciences, 2018)
Background & Aim: insulin injection to the patients suffered from diabetes mellitus need to consider the dose, route, time and injection spot since it will affect to postprandial blood sugar.  This study aimed to determine the effectiverness of insulin injection site and interval timing administration to the control of postprandial glucose in diabetes mellitus patients type 2. Methods & Materials: The study was an experimental with Randomized Complete Block Design (RCBD). The population were patients with diabetes mellitus type 2 in dr. Moewardi Hospital Solo, Indonesia, consisted of 60 respondents taken from simple random sampling (allocate by inverse transform random variate generator and with Microsoft Excel), the respondents were divided into 4 blocks or groups (15 respondents/blocks). Injection used was Rapid-acting insulin with the dosage prescribed by the doctor. Injection was done in four (4) locations; abdomen, deltoid, thigh and gluteus. The administration were 0 minutes (along with meals), 10 minutes before meal, 20 minutes before meal and 30 minutes before meal. Two hour postprandial glucose levels were measured using a Glucometer. Data were then analyzed by SPSS 18 with Two-Way ANOVA and Tukey HSD. Result: 55% of the respondents was male and 45% was female. All respondents were ≥ 40 years old, most of the respondents were in normal body weight and they have suffered the illness >10 years. There were differences in postprandial glucose levels in people with diabetes who obtained insulin injection at the site of the abdominal, deltoid, thigh and gluteus (P <0.05). There were differences in postprandial glucose levels in people with diabetes who obtained insulin injections at 0, 10, 20 and 30 minutes before meal (P <0.05). The location and the most effective time for insulin injection was in the abdomen at time 0 minute before meal (P <0.05). Conclusion:Injection of insulin made in the abdomen by the time of meals effectively controlled postprandial glucose levels in patients with diabetes mellitus type 2.